Perspectives of Malaysian academics on the preparation of fourth industrial revolution for Construction Technology Program - Murni Fahirah Mahmud; Muhamad Afzamiman Aripin; Nur Hazirah Noh Seth; Al Amin Mohamed Sultan; Nur Hidayah Junaidi (International Journal of Evaluation and Research in Education (IJERE), 2023)
The purpose of this study is to examine the perspective of Construction Technology academics from Malaysia vocational colleges on implementing the aspects of the industrial revolution 4.0 (IR 4.0). It was achieved by determining the degree of leadership support for vocational colleges, implementation of IR 4.0 components by academics, readiness for both generic and IR 4.0-related technical skills. This study was conducted using a survey method (cross-sectional study) where data collection and research findings were done only once during this study was conducted by applying the questionnaire method. The sample was chosen from among 408 academics from 42 vocational schools in Malaysia using Fisher's Formula. By choosing to work with a 95% confidence level, a standard deviation of 0.5, and a confidence interval (margin of error) of ± 5%, this study requires 198 samples for a better data findings and analysis. From 198 instruments distributed, only 45 instruments managed to be collected and analyzed due to limitation during global pandemic. The findings of this study were analyzed using Statistical Packages for Social Sciences (SPSS) software, version 20 by taking the mean value of each variable studied. The results of the study showed that the average mean score for each of the overall objectives of the study was at a high level which is between the mean ranges of 3.98 - 4.38. This shows that the level of implementation and readiness from the perspectives of vocational college academics in Malaysia in the field of Construction Technology is at a high level.